NONVERBAL FORMS OF ADDRESS IN UZBEK COMMUNICATION - Nizomova, Zarifa (MMIT Proceedings, 2023)
The article provides a brief overview of paralinguistic tools and their level of study and importance. In the application, non-verbal forms are also extensively analyzed. Linguistic and non-linguistic, interactions and contradictions between them, possibilities of creating a certain image are also discussed. The question of the characteristics of non-verbal means in the process of communication is also covered